2017
DOI: 10.24326/asphc.2017.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Vine Growth and Yield Response of Alphonse Lavallée (V. Vinifera L.) Grapevines to Plant Growth Promoting Rhizobacteria Under Alkaline Condition in Soilless Culture

Abstract: High carbonate content in soil negatively affect plant growth, because the availability of nutrients is restricted due to high pH. The present investigations were carried out to reveal possible alleviating effects of the exogenous root inoculation PGPRs on development and physiology of soilless-grown grapevines cultivated under alkaline stress in controlled glass house. pH of growth medium was increased from 7.5 to the values ranging from 7.9 (control) to 8.1 (A18) according to the bacterial inoculations by Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Transpiration is also highly correlated with current microclimatic conditions, e.g. irradiance and temperature [Sabir and Yazar, 2015;Konarska et al, 2016]. At the leaf level, transpiration rates are controlled both physiologically by stomatal conductance and physically by gas exchange between leaves and the surrounding air [Winbourne et al, 2020].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transpiration is also highly correlated with current microclimatic conditions, e.g. irradiance and temperature [Sabir and Yazar, 2015;Konarska et al, 2016]. At the leaf level, transpiration rates are controlled both physiologically by stomatal conductance and physically by gas exchange between leaves and the surrounding air [Winbourne et al, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…When plants receive enough amounts of water, a correlation between transpiration and VPD exists [Tan et al, 2020]. Midday high temperature and high vapour pressure deficit often result in decrease in stomatal conductance and, consequently in transpiration at noon and/or early afternoon due to temporal drought stress in leaf tissues caused by insufficient water supply from roots [Tuzet et al, 2003;Sabir et al, 2015;Yan et al, 2016]. This contributes to the diurnal pattern of water vapour pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2003) observed Bacillus strains BAI6 and OSU142 increased rooting in 41B (a hardy cross between old-word V. vinifera and new-world V. berlandieri ) rootstocks. Similarly, Sabir (2013) and Sabir et al. (2017) applied P. putida BA-8 and B. simplex T7 to 41B hybrids and recorded a promotion of graft callusing, scion shoot growth, nursery survival rate, and fruitfulness.…”
Section: Microorganisms As Biostimulantsmentioning
confidence: 98%
“…Köse et al (2003) observed Bacillus strains BAI6 and OSU142 increased rooting in 41B (a hardy cross between old-word V. vinifera and new-world V. berlandieri) rootstocks. Similarly, Sabir (2013) and Sabir et al (2017) applied P. putida BA-8 and B. simplex T7 to 41B hybrids and recorded a promotion of graft callusing, scion shoot growth, nursery survival rate, and fruitfulness. Salomon et al (2016) tested a combination of strains B. licheniformis and P. fluorescens in order to improve the growth of V. vinifera cultivar 'Malbec' in greenhouse conditions.…”
Section: Microorganisms As Biostimulantsmentioning
confidence: 98%